Application of Nucleic Acid-Based Strategies to Detect Infectious Pathogens in Orthopaedic Implant-Related Infection. (5th April 2023) - McClure, Emily Ann; Werth, Paul; Ross, Benjamin; Gitajn, Ida Leah
Abstract : ➤ Implant-associated infection in orthopaedic surgery remains an enormous and largely unsolved clinical problem with a high rate of persistent or recurrent infection. This may be due, at least in part, to the potential for underdiagnosis by traditional microbial culture or the potential for culture to incompletely identify the microbial species present. ➤ Nucleic acid-based diagnostic techniques, focused on using the diagnostic information contained in DNA or RNA to identify microbial species, have been developing rapidly and have garnered escalating interest for both clinical and research applications. ➤ Commonly applied techniques include end-point polymerase chain reaction (PCR), quantitative PCR, Sanger sequencing, and next-generation sequencing. Understanding the specific strengths and weaknesses of each technique is critical to understanding their utility, applying the correct assessment strategy, and critically understanding and interpreting research. ➤ The best practices for interpreting nucleic acid-based diagnostic techniques include considering positive and negative controls, reads per sample, detection thresholds (for differentiating contaminants from positive results), and the primer set or targeted regions.